2009
DOI: 10.2353/ajpath.2009.080417
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Roles of Calreticulin in Prostate Cancer Growth and Metastasis

Abstract: Calreticulin is an essential, multifunctional Ca 2؉ -binding protein that participates in the regulation of intracellular Ca 2؉ homeostasis, cell adhesion, and chaperoning. Calreticulin is abundantly expressed and regulated by androgens in prostate epithelial cells. Given the importance of both calreticulin in multiple essential cellular activities and androgens in prostate cancer, we investigated the possibility of a role for calreticulin in prostate cancer progression. Immunohistochemistry revealed the down-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…However, it was also reported that CALR might inhibit growth and/or metastasis of prostate cancer cells in vitro and in vivo (11). Also, cell surface CALR has been considered as an 'eat-me' signal, and cell surface CALR might promote phagocytic uptake of cancer cells by immune systems (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it was also reported that CALR might inhibit growth and/or metastasis of prostate cancer cells in vitro and in vivo (11). Also, cell surface CALR has been considered as an 'eat-me' signal, and cell surface CALR might promote phagocytic uptake of cancer cells by immune systems (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expressions of CALR in the sera of patients with autoimmune diseases were also reported (12). Again, differential expression of CALR was reported in some cancer types, and in some cases CALR low-expression was found to promote cancer growth (11,12). In lung cancer, the expression level of CALR on tumor cell membrane was apparently related with the pathological grade of the tumor (12).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations